Readiness of private universities to adopt blockchain in accounting information systems - Tazkia Ramadina; Suryo Pratolo (Jurnal Akademi Akuntansi, 2024)
Purpose: This study aims to collect empirical data on the impact of three critical variables in blockchain adoption – performance expectancy, effort expectancy, and social influence – on the Intention to use blockchain in private higher education institutions in Indonesia. Using the UTAUT theoretical framework, this study aims to understand how these three factors influence the decision to adopt blockchain technology in accounting information systems. Methodology/approach: This study investigates how private universities in Indonesia perceive the possibility of implementing blockchain technology in the accounting system. By applying the UTAUT model, the study examined three aspects that may influence the willingness to adopt blockchain technology: performance expectancy, effort expectancy, and social influence. Data was collected through distributing questionnaires to 136 leaders of finance departments in various private universities. Findings: The results show that performance and efficacy expectancy significantly influence the Intention to use blockchain technology in private universities. In contrast, social influence does not show a significant influence. Practical and Theoretical contribution/Originality: This research makes a practical contribution by highlighting the importance of perceived usefulness and ease of use in driving blockchain adoption in the higher education sector. From a theoretical perspective, this study extends the applicability of the UTAUT model in the context of private universities in Indonesia. Research Limitation: The Object of this research is only private higher education institutions in Indonesia.